Short chain fatty acids and gut microbiota differ between patients with Parkinson's disease and age-matched controls. (November 2016) - Unger, Marcus M.; Spiegel, Jörg; Dillmann, Klaus-Ulrich; Grundmann, David; Philippeit, Hannah; Bürmann, Jan; Faßbender, Klaus; Schwiertz, Andreas; Schäfer, Karl-Herbert
Abstract: Background: Patients with Parkinson's disease (PD) frequently have gastrointestinal symptoms (e.g. constipation) and exhibit the PD-typical pathohistology in the enteric nervous system (ENS). Both, clinical symptoms and pathohistological changes in the ENS occur at early stages and can precede the motor manifestations of PD. Two recent studies reported an association between changes in gut microbiota composition and PD. We hypothesized that alterations in gut microbiota might be accompanied by altered concentrations of short chain fatty acids (SCFA), one main metabolic product of gut bacteria. Methods: We quantitatively analyzed SCFA concentrations (using gas chromatography) and microbiota composition (using quantitative PCR) in fecal samples of 34 PD patients and 34 age-matched controls. Results: Fecal SCFA concentrations were significantly reduced in PD patients compared to controls. The bacterial phylum Bacteroidetes and the bacterial family Prevotellaceae were reduced, Enterobacteriaceae were more abundant in fecal samples from PD patients compared to matched controls. Conclusions: Our study confirms the recently reported association between PD and the abundance of certain gut microbiota and shows a reduction in fecal SCFA concentrations (one main metabolic product of certain gut bacteria). The reduction in SCFA might, theoretically, induce alterations in the ENS and contribute to gastrointestinal dysmotility in PD. Prospective longitudinal studies in subjects at risk for PD are required to further elucidate the causal role of gut microbiota and microbial products in the development of PD and PD-associated dysmotility. Highlights: The study confirms an association between Parkinson's disease and changes in gastrointestinal microbiota. Fecal short chain fatty acids (SCFA) are reduced in Parkinson's disease. The reduction in SCFA is consistent with the altered gut microbiota composition. The reduction in SCFA might contribute to gastrointestinal dysmotility in Parkinson's disease.